A pH-responsive phase transformation of a sulfonated metal–organic framework from amorphous to crystalline for efficient CO2 capture. Issue 16 (22nd March 2016) - Hu, Zhigang; Lin, Jiajin; Ogiwara, Naoki; Rodriguez, Alvaro; Peng, Yongwu; Wang, Yuxiang; Horike, Satoshi; Zhao, Dan
Abstract : We report a pH-responsive phase transformation of UiO-66-SO3 H from amorphous to crystalline, which is triggered by the neutralization with LiOH, NaOH, or KOH. Abstract : We report a pH-responsive phase transformation of a sulfonated MOF from amorphous UiO-66-SO3 H to crystalline UiO-66-SO3 M (M = Li, Na, K). Such transformation is obtained via neutralizing UiO-66-SO3 H with the according alkali hydroxide solutions. EXAFS and FTIR results suggest that the recovered crystallinity can be attributed to the breakage of strong hydrogen bonds among the sulfonic acids in UiO-66-SO3 H as well as the subsequent charge repulsion in UiO-66-SO3 M to expand the collapsed framework.